Preparation method of high-wear-resistance composite coating on surface of GH4169 high-temperature alloy

Through chemical heat treatment of solid-phase boron permeability and ion beam assisted deposition technology, a boride/Ag composite coating was prepared, which solved the problems of high friction coefficient and insufficient surface hardness of GH4169 nickel-based high-temperature alloy in harsh environments, significantly improving its resistance Abrasiveness and service life.

CN119194343APending Publication Date: 2024-12-27BEIJING RES INST OF AUTOMATION FOR MACHINERY IND
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411487017.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

GH4169 nickel-based high-temperature alloy has a high friction coefficient, insufficient surface hardness, and easy wear, resulting in a short life, limiting its use in key components.

Method used

Chemical heat treatment solid-phase boron permeation method is used to form a boride hard layer on the surface of GH4169 high-temperature alloy, and a solid lubrication Ag layer is added through ion beam-assisted deposition technology to form a boride/Ag composite coating to improve surface hardness and friction performance.

Benefits of technology

It significantly improves the wear resistance and service life of GH4169 high-temperature alloy, reduces contact surface wear, and is suitable for key components in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194343A_ABST
    Figure CN119194343A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a high-wear-resistance composite coating on the surface of a GH4169 high-temperature alloy, and belongs to the technical field of wear-resistant material preparation. According to the preparation method of the high-wear-resistance composite coating on the GH4169 high-temperature alloy surface, a boronizing hard layer is formed on the surface of a GH4169 high-temperature alloy base material by adopting a chemical heat treatment solid-phase boronizing method, and on the basis, a solid lubricating Ag layer is further deposited on the boronizing hard layer by utilizing a novel ion beam assisted deposition method, so that the high-wear-resistance composite coating on the GH4169 high-temperature alloy surface is obtained. And thus, the high-wear-resistance boride / Ag composite coating is formed on the surface of the GH4169 base material. Compared with a traditional nickel-based material, the novel soft and hard composite coating can improve the binding force between a layer and a layer base, the overall quality of a film layer is improved, the friction coefficient is remarkably reduced, and high abrasion resistance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a method for preparing a high wear-resistant composite coating on the surface of a GH4169 high-temperature alloy, in particular, utilizing chemical heat treatment solid phase boronizing and ion-assisted deposition to prepare a hard layer + solid lubricating layer composite coating, belonging to the technical field of wear-resistant material preparation. Background Art

[0002] With the continuous improvement of the performance of key equipment, the materials required in the engine field still need to have the ability to work continuously and stably in harsh environments, and high-temperature alloys are one of the best choices. High-temperature alloys are mainly divided into nickel-based high-temperature alloys, iron-based high-temperature alloys and cobalt-based high-temperature alloys according to the matrix elements. In comparison, nickel-based high-temperature alloys have certain practical application prospects due to their more excellent resistance to high-temperature corrosion. Among them, GH4169 nickel-based high-temperature alloy (Inconel 718) is the most representative nickel-based high-temperature alloy, and is currently widely used in key components such as fasteners, bearings, cast blades and casings of certain engines. However, under harsh working environments (high temperature, high pressure, high speed, etc.), GH4169 alloy has prominent problems such as high friction coefficient, insufficient surface hardness, easy wear and short life, which directly limits its use as a key component, and surface modification can be an important means to solve this problem.

[0003] Chemical heat treatment solid phase boriding refers to the process of placing steel or non-ferrous metal materials in a boron-containing medium, heating them to the boriding temperature and keeping them warm for a period of time, so that boron atoms penetrate into the metal surface to form borides. Chemical heat treatment solid phase boriding technology, through a series of physical and chemical reactions, plays a certain role in strengthening the surface of GH4169 nickel-based high-temperature alloy, and can significantly improve its surface hardness; and this technology has the advantages of simple equipment, controllable thickness of the borided hard layer, excellent bonding with the substrate, and easy operation. At the same time, due to its high surface hardness, it may cause wear on the contact surface, and there will be certain problems in the actual application process. The development of a new wear-resistant coating that has both high hardness and is not easy to wear on the contact surface has become an urgent problem to be solved. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a method for preparing a highly wear-resistant composite coating on the surface of a GH4169 high-temperature alloy. Based on the chemical heat treatment solid phase boriding method, a boride hard coating is deposited on a GH4169 high-temperature alloy substrate. On this basis, an ion-assisted deposition method is adopted to prepare an Ag coating with solid lubrication properties, which can reduce the wear of the contact surface while effectively maintaining the friction coefficient and significantly improve its service life.

[0005] In the present invention, the boride hard coating can be used as a surface supporting layer to make the substrate surface have a certain high hardness and wear resistance; Ag metal has excellent ductility, and the solid lubricating Ag coating prepared by the new process can improve the bonding force with the underlying boride layer, improve the overall deposition quality of the film layer, effectively improve the friction coefficient, and reduce the wear of the contact surface, thereby significantly improving the service life of the substrate.

[0006] The method has simple process, and the thickness of the boride hard coating and the solid lubricating Ag coating is easy to control and can be set according to actual needs, thus having high practical application value.

[0007] To achieve the above technical objectives, the technical solution of the present invention is as follows:

[0008] The present invention provides a method for preparing a high wear-resistant composite coating on the surface of a GH4169 high-temperature alloy, which adopts two methods, chemical heat treatment solid phase boronization and ion beam assisted deposition, to form a boride / Ag composite coating on the surface of a substrate, comprising the following steps:

[0009] S100: pretreatment of substrate, grinding and polishing the GH4169 substrate to be processed to remove grease and impurities attached to the surface of the GH4169 substrate;

[0010] S200, preparing a boride layer, forming a boride layer on the surface of the GH4169 substrate pretreated in step S100 by a chemical heat treatment solid phase boriding method to obtain a boride hard layer;

[0011] S300, preparing an Ag thin film, depositing an Ag thin film on the boride hard layer formed in step S200 by ion beam assisted deposition technology to obtain a solid lubricating Ag layer, that is, forming a boride / Ag composite coating on the surface of the GH4169 substrate;

[0012] As well as S400, the final sample is sealed and the GH4169 substrate with the boride / Ag composite coating formed on the surface is sealed and stored.

[0013] Specifically, in the above-mentioned method for preparing a high-wear-resistant composite coating on the surface of the GH4169 high-temperature alloy, the pretreatment in step S100 includes polishing the surface to 1200# with sandpaper, placing the GH4169 substrate in tetrachloroethylene, acetone solution, and alcohol solution in turn for ultrasonic cleaning, and wiping it dry with a clean silk cloth after each ultrasonic cleaning and placing it in a baking oven to dry.

[0014] In a specific implementation, the preprocessing in step S100 specifically includes:

[0015] S101, grinding the surface of the GH4169 substrate to 1200# with sandpaper;

[0016] S102, placing the GH4169 substrate in tetrachloroethylene for ultrasonic cleaning for 10 minutes, and wiping it dry with a clean silk cloth;

[0017] S103, placing the GH4169 substrate in a 70° C. oven and drying for 20 minutes;

[0018] S104, placing the GH4169 substrate in an acetone solution for ultrasonic cleaning for 10 minutes, and wiping it dry with a clean silk cloth;

[0019] S105, placing the GH4169 substrate in a 70° C. oven and drying for 20 minutes;

[0020] S106, placing the GH4169 substrate in an alcohol solution for ultrasonic cleaning for 10 minutes, and wiping it dry with a clean silk cloth;

[0021] S107, placing the GH4169 substrate in a 70° C. oven and drying for 20 min;

[0022] Specifically, the chemical heat treatment solid phase boronizing process in step S200 includes:

[0023] S201, placing a boronizing agent according to a certain weight in a crucible, placing the crucible and the instrument in a baking oven to dry, and taking out the boronizing agent after drying for standby use; wherein the boronizing agent is a solid powder boronizing agent;

[0024] S202, burying the GH4169 substrate pretreated in step S100 in the dried boronizing agent, and sealing it in a crucible with a sealant;

[0025] S203, placing the sealed crucible into a tube furnace, and introducing argon gas as a protective gas;

[0026] S204, heating the tubular furnace to perform solid phase boronizing heat treatment;

[0027] S205, after the GH4169 substrate described in S204 is cooled to room temperature in the furnace, the boronized GH4169 substrate is taken out;

[0028] S206, lightly grinding the GH4169 substrate described in S205 with 3000# sandpaper to remove the boronizing agent remaining on the surface of the GH4169 substrate;

[0029] S207, placing the GH4169 substrate described in S206 in an alcohol solution for ultrasonic cleaning for 10 minutes, and wiping it dry with a clean silk cloth;

[0030] S208. Place the GH4169 substrate described in S207 in a 70° C. oven and dry for 20 minutes.

[0031] Specifically, the thickness of the borided hard layer after the solid phase boriding heat treatment in step S200 is 1-80 μm, preferably 2-20 μm, and more preferably 4-5 μm. The thickness of the borided hard layer can be controlled by changing the relevant process parameters in step S204.

[0032] Preferably, the heating temperature of the solid phase boronizing heat treatment in step S204 is 600-800°C, and the temperature is kept for 30 minutes. In the actual operation process, the boronizing effect at this temperature can be ensured by selecting a boronizing agent, such as the boronizing agent disclosed in the patent application document with application number 202410145562.9, and other commercially available boronizing agents with a heating treatment temperature in the range of 600-800°C.

[0033] In a specific embodiment, in the chemical heat treatment solid phase boronizing process in step S200, the tube furnace is heated to 600-800°C at a heating rate of 5°C / min and kept warm for 30 minutes. The components of the boronizing agent used include B 4 C, SiC, KBF 4 , Al, where B 4 C is the boron source, KBF 4 As the catalyst, SiC as the filler, Al as the reducing agent, the heat treatment temperature is 700-800℃.

[0034] Specifically, the process of depositing the solid lubricating Ag layer in step S300 includes:

[0035] S301, installing the GH4169 substrate after the boronization heat treatment on the fixture, placing the whole in the vacuum chamber of the ion beam assisted deposition device, and introducing argon gas as a protective gas into the vacuum chamber to make its working gas pressure 1-5Pa, and the purity of argon gas is 99.9%;

[0036] S302, a process of cleaning the surface of the GH4169 substrate using a low energy ion source;

[0037] S303, depositing a Ag thin film on the surface of the GH4169 substrate by a magnetron sputtering method;

[0038] S304, simultaneously with S303, is to use a high-energy ion source to perform an ion-assisted process on the GH4169 substrate, to use a high-energy ion source to perform an ion-assisted process on the GH4169 substrate, to provide high energy while ensuring high Ag ion density, to accelerate deposition, and to improve the bonding force between the Ag layer and the underlying boride layer, thereby improving the overall deposition quality of the film layer;

[0039] S305, after the above steps are completed, cool down with the furnace.

[0040] In a specific implementation, step S302 further includes:

[0041] S3021, low energy ion source cleaning stage is 5-15min, wherein the main arc voltage is 20-40V, the main arc current is 1.2-2.5A, the extraction voltage is 2-3kV, and the extraction current is 100-150mA;

[0042] In a specific implementation, step S303 further includes:

[0043] S3031, During magnetron sputtering, the sputtering voltage is 900V-1000V, the sputtering current is 0.5A-1.0A, and the sputtering gas pressure is 5-10×10 -1 Pa, sputtering time is 100-120min;

[0044] In a specific implementation, step S304 further includes:

[0045] S3041, high energy ion source bombardment stage is 100-120min, wherein the main arc voltage is 50-60V, the main arc current is 1.2-1.5A, the extraction voltage is 5kV, the extraction current is 60mA, the acceleration voltage is 40-50kV, and the acceleration current is 5-15mA.

[0046] The thickness of the solid lubricating Ag layer after ion-assisted deposition in step S300 is 100nm-10μm, preferably 800nm-5μm, and more preferably 1-2μm. The method of simultaneously performing magnetron sputtering and high-energy ion source assisted deposition is adopted, and the thickness of the solid lubricating Ag layer is controlled by changing the relevant process parameters of step S303.

[0047] The technical effects of the present invention are:

[0048] The preparation method of the high wear-resistant composite coating on the surface of GH4169 high-temperature alloy provided by the present invention is combined with two surface modification methods of solid phase boronizing surface heat treatment and ion-assisted deposition. Under harsh working environment (high temperature, high pressure, high speed, etc.), the outstanding problems of high friction coefficient, insufficient surface hardness and poor wear resistance of GH4169 nickel-based high-temperature alloy are effectively overcome, and a new composite coating with adjustable thickness, excellent layer-to-layer bonding strength, self-lubrication and high wear resistance is developed. The coating has good application prospects in the wear-resistant field and is expected to improve the reliability of key components such as engine fasteners, bearings, cast blades and casings in harsh working processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The flowchart and structural schematic diagram of the preparation method of the high wear-resistant composite coating on the surface of GH4169 high-temperature alloy of the present invention;

[0050] Figure 2The room temperature friction coefficient curve of the GH4169 high temperature alloy substrate before and after the preparation of the novel composite coating in Example 1 of the present invention;

[0051] Figure 3 The wear rate bar graph and the wear track graph of the wear scar of the GH4169 high temperature alloy substrate before and after the preparation of the high wear resistant composite coating in Example 1 of the present invention are shown;

[0052] Figure 4 The surface SEM morphology and EDS images of the GH4169 high-temperature alloy substrate prepared in the embodiment of the present invention after the friction test before and after the preparation of the high-wear-resistant composite coating;

[0053] Figure 5 This is a wear scar diagram of the grinding ball surface after a friction test on the GH4169 high-temperature alloy substrate prepared in an embodiment of the present invention before and after the preparation of the high-wear-resistant composite coating.

[0054] Among them, the reference numerals

[0055] 1: Step S100; 2: Steps S201-S204; 3: Steps S205-S208; 4: Step S300; 5: Step S400. DETAILED DESCRIPTION

[0056] In order to better explain the present invention, the present invention is described in detail with reference to the embodiments of the present invention, and the main contents of the present invention are further illustrated in conjunction with specific examples, but the content of the present invention is not limited to the following examples. If no specific technology or conditions are indicated in the examples, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents or instruments is not indicated, they are all conventional products that can be obtained commercially.

[0057] The structural principle and working principle of the present invention are described in detail below in conjunction with the accompanying drawings:

[0058] Chemical heat treatment solid phase boronizing technology is one of the most commonly used methods for surface strengthening of nickel-based high-temperature alloys. During its working process, complex physical and chemical reactions will occur, which are divided into four steps: the generation of active boron atoms, the transfer of active boron atoms, the adsorption of active boron atoms, and the diffusion of active boron atoms. Finally, a boronized layer with a certain thickness, organizational structure and chemical composition different from the substrate can be formed on the inner surface of the substrate. The change in the ratio of different components of the boronizing agent and the chemical heat treatment with appropriate process parameters will significantly improve the hardness and wear resistance of the substrate surface.

[0059] Ion beam assisted deposition technology is also a solid lubricant film preparation technology that has received widespread attention in recent years. It is an ion surface composite treatment technology that combines ion beam injection with magnetron sputtering technology. The process is a simultaneous physical and chemical effect. The physical effects include collision, energy deposition, migration, enhanced diffusion, nucleation, recrystallization and sputtering, and the chemical effects include chemical activation and the formation of new chemical bonds. The coating film prepared by this technology has a high bonding strength to the substrate. At the same time, it solves the dual problems of low deposition ion density caused by long ion injection working distance and small target material, and low deposition efficiency and poor bonding force caused by low magnetron sputtering energy. It can efficiently grow a solid lubricant film with certain characteristics that are completely different from the substrate.

[0060] See also Figure 1 , Figure 1 The present invention is a preparation method of a high wear-resistant composite coating on the surface of a GH4169 high temperature alloy and a schematic diagram of its structure.

[0061] The present invention is based on the chemical heat treatment solid phase boriding method, and deposits a certain thickness of boride hard coating on the GH4169 high-temperature alloy substrate, which can be used as a surface support layer to make the substrate surface have a certain high hardness and wear resistance. On this basis, an ion-assisted deposition method is adopted to prepare an Ag coating with high bonding force and solid lubrication performance. This layer can effectively improve the friction coefficient and reduce the wear of the contact surface, significantly improving the service life of the GH4169 high-temperature alloy.

[0062] Example 1 Preparation of high wear-resistant composite coating on the surface of GH4169 high-temperature alloy

[0063] The specific steps include the following:

[0064] Step S100, pretreatment of the substrate, pretreatment of the GH4169 substrate to be processed, grinding and polishing the substrate surface to meet the surface heat treatment requirements, and removing grease and impurities attached to the substrate surface; the specific process includes:

[0065] Step S101, polishing the surface of the GH4169 substrate with 180#, 400#, 800#, and 1200# sandpapers in sequence;

[0066] Step S102, placing the polished GH4169 substrate in non-polluting tetrachloroethylene for ultrasonic cleaning for 10 minutes, taking it out and wiping it clean with a clean silk cloth;

[0067] Step S103, placing the substrate in a 70° C. oven and drying for 20 minutes;

[0068] Step S104, the substrate is further placed in a non-polluting acetone solution for ultrasonic cleaning for 10 minutes, and then taken out and wiped clean with a clean silk cloth;

[0069] Step S105, placing the substrate in a 70° C. oven and drying for 20 minutes;

[0070] Step S106, finally, the substrate is placed in a non-polluting alcohol solution for ultrasonic cleaning for 10 minutes, and then taken out and wiped clean with a clean silk cloth; when drying, the polished surface of the substrate is wiped in the same direction to ensure that there is no water stain or impurity residue on the surface of the substrate;

[0071] Step S107, placing the GH4169 substrate in a 70° C. oven and drying for 20 minutes.

[0072] Step S200, preparing a boride layer, forming a 4-5 μm boride layer, i.e., a boride hard layer, on the surface of the GH4169 substrate by a chemical heat treatment solid phase boriding method; the specific process includes:

[0073] Step S201, put a certain weight of boronizing agent into a crucible, put it in a 100°C oven together with the crucible and instruments, and dry it for 120 minutes. After drying, take it out for use; the boronizing agent is a commercially available solid powder boronizing agent, and its main components include B 4 C, SiC, KBF 4 , Al, etc., among which B 4 C is the boron source, KBF 4 As a catalyst, SiC as a filler, and Al as a reducing agent;

[0074] Step S202, burying the pretreated substrate in the dried boronizing agent and sealing it in a ceramic crucible using a sealant;

[0075] Step S203, placing the sealed crucible into a tube furnace, and introducing argon as a protective gas, with an argon flow rate of 60 mm; at the same time, the argon needs to be circulated in the furnace before taking out the GH4169 substrate;

[0076] Step S204: The working parameters of the tube furnace should be set to gradually heat to 600-700°C at a heating rate of 5°C / min and keep warm for 30 minutes, so as to perform solid phase boronizing heat treatment to form a boronized hard layer on the surface of the GH4169 substrate;

[0077] Step S205, after the reaction is completed, wait for the GH4169 substrate to cool down to room temperature in the furnace, and then take out the boronized GH4169 substrate;

[0078] Step S206, lightly polish the boronized GH4169 substrate using 3000# sandpaper to remove the boronizing agent remaining on the surface of the GH4169 substrate. At this time, the surface state of the GH4169 substrate should not affect the next step of ion beam assisted deposition operation;

[0079] Step S207, placing the polished GH4169 substrate in an alcohol solution for ultrasonic cleaning for 10 minutes, and wiping it dry with a clean silk cloth;

[0080] Step S208: Finally, the GH4169 substrate is placed in a 70° C. oven and dried for 20 minutes.

[0081] At this time, the surface of the GH4169 substrate after chemical heat treatment and solid phase boronizing surface treatment is uniform dark gray, no wear marks are seen on the surface after grinding, the Vickers hardness is significantly increased from 445HV to 1572HV, and the presence of boride phase is detected, indicating that a boride layer exists on the surface of the substrate at this time.

[0082] Step S300, preparing an Ag film, and depositing a solid lubricating Ag layer on the boronized hard layer in S200 by ion beam assisted deposition technology; the specific process may include:

[0083] Step S301, install the GH4169 substrate after solid phase boronization by chemical heat treatment on the fixture, and place the whole in the vacuum chamber of the ion beam assisted deposition device, and introduce argon gas into the vacuum chamber as a protective gas. Before taking out the GH4169 substrate, the argon gas should be continuously circulated, and its working gas pressure is 1-5Pa, and the purity of the argon gas is 99.9%;

[0084] Step S302: using a low-energy ion source to clean the surface of the GH4169 substrate; the process includes:

[0085] Step S3021, the low-energy ion source performs surface cleaning on the GH4169 substrate for 5 minutes, wherein the main arc voltage is 20-40V, the main arc current is 1.2-2.5A, the extraction voltage is 2-3kV, the extraction current is 100-150mA, and the cleaning time is controlled within 5-10 minutes;

[0086] Step S303, depositing a 1-2 μm thick Ag coating on the surface of the GH4169 substrate by magnetron sputtering; the process includes:

[0087] Step S3031: During magnetron sputtering, the sputtering voltage is 900V-1000V, the sputtering current is 0.5A-1.0A, and the sputtering gas pressure is 5-10×10 -1 Pa, the sputtering time is 100-120min, and the arcing situation must be observed in front of the window before sputtering begins;

[0088] Step S304, which is carried out simultaneously with step 303, is to use a high-energy ion source to perform an ion-assisted process on the GH4169 substrate; after the target material is bombarded by magnetron sputtering, Ag atoms on the surface of the target material will splash out, and at this time, the density of Ag atoms (atomic clusters) is high, but the energy is low. At the same time, the argon ions of the high-energy ion source are accelerated by a high-voltage electric field and collide with Ag atoms (atomic clusters), so that they obtain high energy, and finally accelerate to bombard the surface of the substrate for nucleation and growth; this process of using a high-energy ion source for ion-assisted can ensure high density of Ag ions while providing high energy, accelerate deposition, and at the same time improve the bonding force between the Ag layer and the underlying boride layer, and improve the overall deposition quality of the film layer; the process includes:

[0089] Step S3041, high energy ion source bombardment stage is 100-120min, wherein the main arc voltage is 50-60V, the main arc current is 1.2-1.5A, the extraction voltage is 5kV, the extraction current is 60mA, the acceleration voltage is 40-50kV, and the acceleration current is 10-15mA

[0090] Step S305: After the above steps are completed, the furnace is cooled for 120 minutes.

[0091] At this time, the surface of the GH4169 substrate after secondary surface treatment by ion beam assisted deposition technology appears uniform silver-white, the surface film layer is uniform and dense, and the presence of Ag phase is detected, indicating that there is an Ag layer on the surface of the substrate at this time.

[0092] Step S400, sealing the final sample, covering the GH4169 substrate with the boride / Ag composite coating formed on the surface with degreasing paper and dust-free paper, and then vacuum sealing and storing it.

[0093] See also Figure 2 , Figure 2 The room temperature friction coefficient curve of the GH4169 high temperature alloy substrate before and after the preparation of the high wear-resistant composite coating in Example 1 of the present invention; the friction and wear analysis of the GH4169 substrate was performed by a friction and wear tester. At room temperature and the same air humidity environment, the friction and wear tester was preheated for 20 minutes and tested under high load and high speed test conditions. The friction coefficient of the GH4169 high temperature alloy substrate is relatively high at the beginning of friction and wear. Due to the influence of the surface roughness after grinding, the overall fluctuation is obvious, and its average friction coefficient reaches 0.79; after composite surface modification, due to the presence of the surface lubricating Ag layer, the friction coefficient slowly shows a slow upward trend from the beginning, and the friction curve is relatively smooth as a whole. Since the boride layer under the Ag layer can be used as a supporting layer, the subsequent friction coefficient does not show a significant increase, and its average friction coefficient is 0.42, which is close to half of the substrate. The friction coefficient of the GH4169 substrate (GH4169-B-Ag) after composite surface modification is significantly reduced.

[0094] See also Figure 3 , Figure 3 The wear rate bar graph and the wear track graph of the wear scar of the GH4169 high-temperature alloy substrate before and after the high-wear-resistant composite coating is prepared in Example 1 of the present invention; the wear rate and wear track of the GH4169 substrate are further determined by laser confocal microscopy. The wear rate of the GH4169 high-temperature alloy substrate is 2.7×10 -4 mm 3 / N×m, the wear depth is close to 20μm, and the wear rate of the GH4169 substrate (GH4169-B-Ag) after composite surface modification is 5.0×10 -6 mm 3 / N×m, which is reduced by nearly two orders of magnitude, and the wear depth does not change significantly, which fully proves that the composite surface modification treatment significantly improves the wear resistance of the GH4169 high-temperature alloy substrate.

[0095] See also Figure 4 , Figure 4 a-4b are respectively the surface SEM morphology and EDS images of the GH4169 high-temperature alloy substrate in Example 1 of the present invention after the friction test before and after the preparation of the high-wear-resistant composite coating; the morphology of the wear marks on the surface of the GH4169 substrate is characterized by scanning electron microscopy (SEM), and the surface elements of the wear marks are analyzed by EDS energy spectrum. (a) The wear marks on the surface of the GH4169 high-temperature alloy substrate are relatively wide, reaching 789.17μm, with obvious peeling, wear debris and furrows, and the wear mechanism is abrasive wear; (b) The wear marks on the surface of the GH4169 substrate after the composite surface modification treatment are significantly narrowed, only 193.08μm, no obvious peeling and wear debris are seen, and a enamel layer is formed. The wear mechanism is adhesive wear. EDS analysis shows that the wear marks contain 99.85% Ag elements, which proves the excellent anti-friction and lubrication properties of the composite layer.

[0096] See also Figure 5 , Figure 5 ab are respectively the wear scars on the grinding ball surface of the GH4169 high temperature alloy substrate in Example 1 of the present invention after the friction test before and after the preparation of the high wear-resistant composite coating; the analysis was performed using an optical microscope. (a) The wear scar on the grinding ball surface of the GH4169 high temperature alloy substrate is as wide as 845.29 μm, while (b) the wear scar on the grinding ball surface of the GH4169 substrate after the composite surface modification treatment is only 378.80 μm.

[0097] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work, including changes in various working parameters, belong to the scope of protection of the present invention.

Claims

1. A method for preparing a high wear-resistant composite coating on the surface of a GH4169 high-temperature alloy, characterized in that: The steps include: S100: pretreatment of substrate, grinding and polishing the GH4169 substrate to be processed to remove grease and impurities attached to the surface of the GH4169 substrate; S200, preparing a boride layer, forming a boride layer on the surface of the GH4169 substrate by a chemical heat treatment solid phase boriding method to obtain a borated hard layer; S300, preparing an Ag thin film, depositing an Ag thin film on the boride hard layer by ion beam assisted deposition technology to obtain a solid lubricating Ag layer, that is, forming a boride / Ag composite coating on the surface of the GH4169 substrate.

2. The method for preparing a high wear-resistant composite coating on the surface of a GH4169 high temperature alloy as claimed in claim 1, characterized in that: The pretreatment process in step S100 includes: grinding the surface with sandpaper to 1200#, placing the GH4169 substrate in tetrachloroethylene, acetone solution, and alcohol solution for ultrasonic cleaning in sequence, wiping it with a clean silk cloth after each ultrasonic cleaning and placing it in a baking oven to dry.

3. The method for preparing a high wear-resistant composite coating on the surface of GH4169 high temperature alloy according to claim 1, characterized in that: The chemical heat treatment solid phase boronizing process in step S200 includes: S201, placing the boronizing agent in a crucible, placing the crucible and the crucible in a baking oven for drying, and taking them out for use after drying; S202, burying the GH4169 substrate pretreated in step S100 in the dried boronizing agent, and sealing it in a crucible with a sealant; S203, placing the crucible sealed in step S202 into a tube furnace, and introducing argon gas as a protective gas; S204, heating the tube furnace to 600-800° C., keeping the temperature for 30-480 min, and performing solid phase boronizing heat treatment on the GH4169 substrate; S205, cooling the GH4169 substrate treated in step S204 to room temperature in the furnace, and taking out the GH4169 substrate after solid phase boronizing heat treatment; S206, lightly grinding the GH4169 substrate after the solid phase boronizing heat treatment with sandpaper to remove the boronizing agent remaining on the surface of the GH4169 substrate; S207, placing the polished GH4169 substrate in an alcohol solution for ultrasonic cleaning, and wiping it dry with a clean silk cloth; S208, placing the GH4169 substrate after ultrasonic cleaning in a drying oven.

4. The method for preparing a high wear-resistant composite coating on the surface of GH4169 high temperature alloy according to claim 1, characterized in that: The thickness of the boronized hard layer formed on the surface of the GH4169 substrate in step S200 is 1-80 μm.

5. The method for preparing a high wear-resistant composite coating on the surface of GH4169 high temperature alloy according to claim 1, characterized in that: The process of depositing and forming a solid lubricating Ag layer in step S300 includes: S301, mounting the GH4169 substrate with the boronized hard layer formed on the surface onto a fixture, placing the entire substrate in a vacuum chamber of an ion beam assisted deposition device, introducing argon gas as a protective gas into the vacuum chamber to make the working pressure of the vacuum chamber 1-5 Pa, and the purity of the argon gas being above 99.9%; S302, using a low-energy ion source to perform a surface cleaning process on the GH4169 substrate; S303, depositing a Ag thin film on the surface of the boronized hard layer of the GH4169 substrate by a magnetron sputtering method; S304, simultaneously with step S303, using a high energy ion source to perform ion assistance on the process of depositing the Ag coating; S305, cooling the GH4169 substrate on which the Ag film is deposited along with the furnace.

6. The method for preparing a high wear-resistant composite coating on the surface of GH4169 high temperature alloy as claimed in claim 5, characterized in that: The step S302 further comprises: S3021. During the low-energy ion source cleaning stage, the main arc voltage is 20-40V, the main arc current is 1.2-2.5A, the extraction voltage is 2-3kV, the extraction current is 100-150mA, and the cleaning time is controlled at 5-15min.

7. The method for preparing a high wear-resistant composite coating on the surface of a GH4169 high temperature alloy as claimed in claim 5, characterized in that: The step S303 further comprises: S3031, During magnetron sputtering, the sputtering voltage is 900V-1000V, the sputtering current is 0.5A-1.0A, and the sputtering gas pressure is 5-10×10 -1 Pa, sputtering time is 100-200min.

8. The method for preparing a high wear-resistant composite coating on the surface of GH4169 high temperature alloy as claimed in claim 5, characterized in that: The step S304 further comprises: S3041. During the high energy ion source bombardment stage, the main arc voltage is 50-60V, the main arc current is 1.2-1.5A, the extraction voltage is 5kV, the extraction current is 60mA, the acceleration voltage is 40-50kV, the acceleration current is 5-15mA, and the high energy ion source bombardment time is 100-200min.

9. The method for preparing a high wear-resistant composite coating on the surface of GH4169 high temperature alloy according to claim 1, characterized in that: In the step S300, the thickness of the solid lubricating Ag layer formed by ion-assisted deposition is 100 nm-10 μm.

10. The method for preparing a high wear-resistant composite coating on the surface of GH4169 high temperature alloy according to claim 3, characterized in that: The boronizing agent is a solid powder boronizing agent, including B4C, wherein B4C is a boron source.

Citation Information

Cited By

  • Novel multi-layer multi-element plunger piston coating based on ion nitriding and ion implantation treatment and preparation method and application of novel multi-layer multi-element plunger piston coating

    CN121380825A

  • Wear-resisting and friction-reducing plunger composite coating based on ion implantation treatment and preparation method and application of wear-resisting and friction-reducing plunger composite coating

    CN121380874A